ANALISIS UNSUR PENGIMAJIAN PADA PUISI “DI NEGERI AMPLOP” KARYA MUSTOFA BISRI - Kusuma, Dewi (LPPM UNU CIREBON, 2024)
Mustofa Bisri's poems are known as polite, grammatical and subtle. With an arrangement of structures that form a series of beautiful and meaningful words. Apart from having high aesthetics and being full of meaning to be expressed to the reader, this poem is also an outpouring of the author's heart through its building blocks, namely the physical structure and inner structure. Each poem contains a message which is the result of the author's expression and creativity. This research will examine the elements of imagery contained in the poem